2005
DOI: 10.1177/1097184x04268800
|View full text |Cite
|
Sign up to set email alerts
|

Trouble with Conscription, Entertaining Soldiers

Abstract: Gender and military studies focus on Western postconscription societies, overlooking the significance of military service to gender order in the larger society. Concerned with the military's changing form in industrial and democratic society, military sociology literature argues for the broad trend toward the decline of the conscription-based military and highlights not only economic factors but also geopolitical factors influencing this trend. Yet this literature overlooks the significance of gender in interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…By contrast, masculinity remained, until recently-as Todd Reeser has observed in the context of European masculinitiesinvisible as an object of academic enquiry beyond providing a discursive structure against which analyses of patriarchal oppression were conducted (2010: 16-21). It was not until Korean scholars began to illustrate how hegemonic masculinities are tied to notions of militarised masculinity and national identity that we have begun to draw the contours of how hegemonic masculinities continue to underlie notions of citizenship as a community of men (Choi 1998;Han & Ling 1998;Moon 1998Moon , 2005. This link between idealised hypermasculinity and authoritarian statehood has been further advanced by other scholars (Murphree 2008).…”
Section: University Of Western Australiamentioning
confidence: 97%
“…By contrast, masculinity remained, until recently-as Todd Reeser has observed in the context of European masculinitiesinvisible as an object of academic enquiry beyond providing a discursive structure against which analyses of patriarchal oppression were conducted (2010: 16-21). It was not until Korean scholars began to illustrate how hegemonic masculinities are tied to notions of militarised masculinity and national identity that we have begun to draw the contours of how hegemonic masculinities continue to underlie notions of citizenship as a community of men (Choi 1998;Han & Ling 1998;Moon 1998Moon , 2005. This link between idealised hypermasculinity and authoritarian statehood has been further advanced by other scholars (Murphree 2008).…”
Section: University Of Western Australiamentioning
confidence: 97%
“…Participants had mixed feelings towards their military service and masculinities constructed during their service. On the one hand, given that military service is one of the few experiences the majority of adult Korean men share with one another (Moon, 2005b), participants believed that they would not be excluded from mainstream society. On the other hand, however, they identified that their self-conceptualizations of masculinity did not fit masculine ideals in the military.…”
Section: Construction Of Militarized Masculinities As a Complex Processmentioning
confidence: 99%
“…With regard to hegemonic masculinity in Korea, discussions have been had, in particular, on militarized masculinities in various contexts, such as the nation-state building process of the Korean Peninsula (Moon 2005a), the military conscription system (Moon 2005b), and military unionism (Kwon 2005). Even though there have been some meaningful endeavors to clarify business masculinity in Korea (e.g., Kim and Park 2003;Lee and Parpart 2018;Song 2003), the literature still lacks the agency of the top managers, inasmuch as researchers have been limited to analyzing autobiographies, company advertisements, and corporate social responsibility reports.…”
Section: Literature Reviewmentioning
confidence: 99%